Pengaruh Foreign Direct Investment, Governement Expenditure, Dan The Nexus Remittance Terhadap Sustainbility Economic Growth Di Asean Tahun 2017-2022 Dalam Perspektif Ekonomi Islam - Sholekah, Fadhila Amallya; Sisdianto, Ersi; Bahtiar, Muhammad Yusuf (Cattleya Darmaya Fortuna, 2024)
Sustainable economic growth is needed to support the welfare of ASEAN people. Increasing sustainable economic growth that does not support environmental sustainability, welfare, infrastructure and social justice will actually make people further away from the expectations they want to achieve, because it will create new problems that are more fatal and complex. This study aims to analyze the effect of foreign direct investment, government expenditure, and the nexus remittance on the sustainability of economic growth in ASEAN during the period 2017-2022 from an Islamic economic perspective. The analysis method used is panel data regression analysis with secondary data sources obtained from the World Bank. The appropriate model is the Fixed Effect Model (FEM). The results of the study show that foreign direct investment has no effect on the sustainability of economic growth, government expenditure has a positive effect on the sustainability of economic growth and the nexus remittance has a positive effect on the sustainability of economic growth .